Effect of maturity stage on the nutritive vaule of native grass hay - Rao, M.R.; Harbers, L.H.; Latschar, A.M.; Smith, E.F. (Kansas State University. Agricultural Experiment Station, 2011)
The evaluation of pastures by esophageally fistulated steers requires artificial rumen techniques to determine digestibilities of grasses. To develop a regression curve between data obtained by an artificial rumen and those from a grazing animal, we conducted a series of metabolism studies and artificial rumen trials using native prairie hay from the Flint Hill area cut at three maturity stages.
Keywords: Beef; Grass Hay; Maturity